Dissipation process of binary gas mixtures in thermally relativistic flow. (28th April 2016) - Yano, Ryosuke
Abstract: In this paper, dissipation process of binary gas mixtures in thermally relativistic flows is discussed with focus on characteristics of diffusion flux. As an analytical object, we consider the relativistic rarefied-shock layer around a triangular prism. Numerical results for the diffusion flux are compared with the Navier–Stokes–Fourier (NSF) order approximation of the diffusion flux, which is calculated using the diffusion and thermal-diffusion coefficients by Kox et al (1976 Physica A 84 165 –74 ). In the case of uniform flow with small Lorentz contraction, the diffusion flux, which is obtained by calculating the relativistic Boltzmann equation, is roughly approximated by the NSF order approximation inside the shock wave, whereas the diffusion flux in the vicinity of a wall is markedly different from the NSF order approximation. The magnitude of the diffusion flux, which is obtained by calculating the relativistic Boltzmann equation, is similar to that of the NSF order approximation inside the shock wave, unlike the pressure deviator, dynamic pressure and heat flux, even when the Lorentz contraction in the uniform flow becomes large, because the diffusion flux does not depend on the generic Knudsen number from its definition in Eckart's frame. Finally, the author concludes that for accuracy diffusion flux must be calculated using the particle four-flow and averaged four velocity, which are formulated using the four velocity defined by each species of hard spherical particles.